STRATEGIC TRANSFORMATION TOWARD INITIAL PUBLIC OFFERING (IPO): A CASE STUDY OF BANK JAKARTA AS A REGIONAL DEVELOPMENT BANK - Hasta Asymar Herlan; Syukron Sazly (Dynamic Management Journal, 2026)
The transformation of regional development banks (RDBs) into publicly listed companies has become a strategic issue amid increasing competition, digital disruption, and the growing demand for transparency and professional governance in the banking industry. This study aims to explore the strategic transformation process toward Initial Public Offering (IPO) readiness in Bank Jakarta, a regional development bank owned by the Jakarta Provincial Government. Using a qualitative single-case study approach, this research analyzes secondary data from annual reports, sustainability reports, corporate disclosures, and regulatory documents during the 2020–2025 period. The analysis focuses on four strategic capabilities influencing IPO readiness: corporate governance capability, digital transformation capability, risk management capability, and financial capability. The findings reveal that IPO preparation is not merely a capital-raising strategy but a comprehensive organizational transformation process. Bank Jakarta has strengthened financial performance, expanded lending capacity, improved governance practices, accelerated digital transformation, and enhanced risk management as key foundations for becoming a public company. This study proposes a Strategic IPO Readiness Framework for Regional Development Banks, explaining how internal organizational capabilities support transformation toward a publicly listed institution.  Practically, the findings provide strategic insights for policymakers and RDB managers in designing sustainable IPO transformation strategies.